0
$\begingroup$

Assume that we have a moving average like this:

$E_t = a*S_{t-1}+(1-a)*E_{t-1}$

where $E$ would be an estimate we are interested in, and $S$ is a sample we take at each point in time.

Now, if we knew say three samples (e.g. at $t = 0,1,2$ and currently $t = 3$), we could get the current $E$ by calculating $E$ at each point in time and plugging that into the next one, like this:

$E_1 = a*S_0 + (1-a)*E_0$

$E_2 = a*S_1 + (1-a)*E_1$

$E_3 = a*S_2 + (1-a)*E_2$

Now, I would like to understand, how would I generalize this to $n$ samples? So that we would not need to do everything step by step like that.

$\endgroup$
0
$\begingroup$

$$E_n = (1-a)^n E_0 +a \sum_{i=1}^n (1-a)^{n-i}S_i$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.